2016
DOI: 10.1116/1.4945306
|View full text |Cite
|
Sign up to set email alerts
|

Positively charged supported lipid bilayer formation on gold surfaces for neuronal cell culture

Abstract: Supported lipid bilayers are widely used as cell membrane models and sensor platforms, but the usage on gold surface needs additional surface modification or optimized experimental conditions. In this work, the authors show lipid bilayer formation on plasma activated gold surfaces in physiological conditions without any other modification if at least 30% positively charged lipids are present. Details of bilayer formation from small unilamellar vesicles were monitored using quartz crystal microbalance with diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The negative values of the ζ-potentials for the three pure lipid samples are in the order POPC>DPPC>DOPC, which is in agreement with the previous reports 28,29) . These increase dramatically with the addition of 0.075 mole fraction of PSO 4 .…”
Section: Size and ζ-Potentialsupporting
confidence: 93%
“…The negative values of the ζ-potentials for the three pure lipid samples are in the order POPC>DPPC>DOPC, which is in agreement with the previous reports 28,29) . These increase dramatically with the addition of 0.075 mole fraction of PSO 4 .…”
Section: Size and ζ-Potentialsupporting
confidence: 93%
“…However, although this is a straightforward procedure in the case of hydrophilic surfaces ( i.e. , glass), hydrophobic substrates require pretreatments to adjust the surface tension or specific lipid mixtures to promote surface adhesion (Figure A). , To overcome such limitations, solvent-assisted lipid bilayer (SALB) formation might be achieved by rapid solvent exchange from an organic to an aqueous solution, promoting bilayer formation and the possible incorporation of TMPs . Finally, moving toward fully biological membranes, cell blebbing enables the collection of cell membrane vesicles to form a bilayer with proteins that preserves their native conformations and orientations .…”
Section: Functionalization Of Organic Transistors With Biomembranesmentioning
confidence: 99%
“…However, on 1,2-dioleoyl-3-trimethylammoniumpropane (DOTAP) 30% SLB, only dead cells fluoresce, meaning that live cells are able to resist this transfer process, whereas on DOTAP 100% SLB, both live and dead cells fluoresce. Reprinted and adapted with permission from ref . Copyright 2016 American Vacuum Society.…”
Section: Functionalization Of Organic Transistors With Biomembranesmentioning
confidence: 99%
“…Yet, the nature of the platform presents not only advantages but also challenges. Although it was shown that some types of cells are able to survive on the unmodified surface of planar solid-supported lipid bilayer (SLB), the biologically inert nature of the lipid headgroups does not provide a starting point for adhesion complex formation. To facilitate cell adhesion, additional functionalization is required, for example, by covalent attachment of components of the ECM , or by surfactant-assisted insertion of transmembrane proteins …”
Section: Introductionmentioning
confidence: 99%